Validation of the EdSocEval_V2.: Use, training and assessment of ICT in Social Education (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
The objective is the development and validation of a tool that allows us to obtain information on the use, training and valuation of ICT among social educators. A review is carried out by means of expert judgment, calculation of internal consistency by means of Cronbach's alpha and factor analysis. It was applied to a sample of 504 professionals. The level of internal consistency is high (0.891) and shows a factorial structure in eight factors that explain 60.2 of the variance. The proposed tool is useful for its objectives. We highlight the interest of the tool due to the interrelation of the three measures.